Evaluation of Asymmetric Dimethylarginine, Malondialdehyde, and Vitamin Levels of Borderline Personality Disorder Patients With and Without Self-Mutilation - Telo, Selda; Baykara, Sema (Korean Neuropsychiatric Assoc, 2023)
Objective Believing that oxidative stress may be increased in borderline personality disorder (BPD) patients with self-mutilating behaviors (SMB), we aimed to measure serum asymmetric dimethylarginine (ADMA) and malondialdehyde (MDA) levels in these patients. Methods The study included 60 patients diagnosed with BPD and 30 healthy controls. BPD patients were divided into two groups: 30 female patients with SMB and 30 female patients with no-self-mutilating behavior (NSMB). ADMA, MDA, vitamin A, and vitamin E levels were analyzed. Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI) were conducted with the participants. Results Serum ADMA and MDA levels were higher in SMB and NSMB group compared to control group. Serum vitamin E levels were also lower in the SMB group compared to the control group. Positive correlations were determined between both ADMA and MDA, and between BDI and BAI scores. Also, BAI scores were statistically higher in SMB group compared to NSMB group. Conclusion It was discovered that levels of ADMA and MDA, which reflected oxidative stress, were elevated in patients with BPD who exhibited SMB. Accordingly, future studies should investigate the role of oxidative stress in a more comprehensive way in terms of the different mechanisms underlying and treatments involved in borderline personality disorder.
Keywords: Borderline personality disorders; Self mutilating behavior; Asymmetric dimethylarginine; Malondialdehyde.